Time's Causal Power : Proclus and the Natural Theology of Time - Vargas, Antonio Luis Costa, (Philosophia Antiqua ;, 2021)
This is the first monograph dedicated entirely to Proclus' theory of time, showing the roots of his obscure claim that time is a god and a cause in his reception of Plato, Aristotle, the Stoics and Plotinus. Proclus' theory of time appears as a natural theology, a reasoned ascent to divine principles starting from natural phenomena (in particular, from natural cycles and their synchronization). This theological approach to time develops the pioneering psychological approach of Proclus' predecessor Plotinus, anchoring time not in the world soul, but in the divine unchanging source of the world soul's life.